PENINGKATAN KEDISIPLINAN MELALUI BIMBINGAN KELOMPOK MENGGUNAKAN TEKNIK SELF-MANAGEMENT PADA SISWA KELAS XI DKV SMK KRISTEN BISNIS DAN MANAJEMEN SALATIGA - Mosa, Adrian Dandi Woda; Soesilo, Tritjahjo Danny; Agustin, Adhi Krisna Maria (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine the significance of increased discipline through group guidance with self-management techniques for XI Visual Communication Design students at Christian Business & Management Vocational School, Salatiga. This type of research is a quasi-experiment. The sample in this research were 13 XI Visual Communication Design students who had a low level of discipline. This research data collection technique uses a disciplinary scale. The data analysis technique used is Mann-Whitney. The research results show that there are significant differences in student discipline as evidenced by the results of the Asymp analysis. Sig. (2-tailed) 0.003 < 0.05. The average mean rank in the experimental group was 82% and the control group was 0.06%, those ho was rejected and H1 was accepted because there was an increase in the level of student discipline after being given group guidance services with self-management techniques to students.